Respuesta :

Dev921
First rearrange the second equation and isolate for Y so x-y=6 would become -y=6-x but you can’t hav a negative Y so divide everything by -1 so you end up with y=x-6

Now plug it in the first equation so
X+(x-6)=4 and solve it
Your gonna get x=5

You don’t need to solve For y because in all the options you listed only One has 5 as the x value so u can assume the answer is (5,-1)

The solution to the system of linear equations is: C. (5, -1)

What is the Solution of a System of Linear Equations?

The solution is the value of x and y coordinates of the point where the line of the two linear equations intersect.

Thus, given the system:

x + y = 4 --> Eqn. 1

x - y = 6 --> Eqn. 2

Rewrite Eqn. 1

x = 4 - y

Substitute x = (4 - y) into eqn. 2.

(4 - y) - y = 6

4 - 2y = 6

-2y = 6 - 4

-2y = 2

y = -1

Substitute y = -1 into Eqn. 1 to find x

x + (-1) = 4

x - 1 = 4

x = 4 + 1

x = 5

Therefore, the solution to the system of linear equations is: C. (5, -1)

Learn more about system of linear equations on:

https://brainly.com/question/14323743

ACCESS MORE